Co-Management of Protected Areas: A Governance System Analysis of Vatnajökull National Park, Iceland - Jon Geir Petursson; Dadi Mar Kristofersson (Land, 2021)
Land allocated to protected areas (PA) is expanding as are expectations about the services these areas deliver. There is a need to advance knowledge on PA governance systems, like co-management, recognising that there is no “one-size-fits-all” solution. We analyse the co-management governance system and performance of Vatnajökull National Park (VNP), Iceland. We adapt an analytical framework from the literature on environmental governance and analyse its governance system, hence actor roles, institutional arrangements and interactions. Our findings illustrate that the co-management structure was an outcome of political negotiations and a response to the lack of legitimacy of its predecessors; resulting in a tailor-made governance system set out in park-specific legislation. Although the performance is quite positive, being adaptive to changes, inclusive, promoting rural development and an appreciated facilitator of devolution and power-sharing, it has come with challenges. It has encountered problems delineating responsibilities among its actors, causing conflict and confusion; in settling conflicting localised issues close to local stakeholders, there have been capacity issues. We argue that the VNP co-management system is fit for its purpose, aligned with Icelandic land-use governance structures but in need of systematic improvements. There are important lessons as Iceland seeks to expand its PA estate and beyond, since the global community is setting ambitious policy goals to expand site-based conservation.